Foreign policy of united national front government - a study - Ganeshalingam, K.T. (Faculty of Graduate Studies University of Jaffna, 2004)
The United National Front's Government is trying to make its foreign policy in two dimensions. The first one is Developmental aspects of Srilankan economy and the Second one is the Srilankan National integrity Sovereignty and Security of Nation. The Government of UNF Led by Ranil Wiekramasinha devised its foreign Policy in such a way that obviously supports the western stance in many aspects As a result of this diplomatic move, the Srilankan Government is benefited in various ways. For Example the records indicate that there is a huge increase in the economical aids supplied by the western Countries to Srilanka. In the meantime, the coalition Government has resorted to a strategy convincing India that they accommodate the Indian security policy rather than western security policy. But the Srilankan Government is not prepared to incorporate any views suggested by Indian their agenda economic development.